RECOGNITION SITES OF RESTRICTION ENDONUCLEASES ON THE GENOMIC DNA OF TWO STARCH BRANCHING ENZYMES FROM CASSAVA (MANIHOT ESCULENTA CRANTZ) - O., JELILI T.; O., OLUFEMI O.; A., OLUYEMISI A.; I., IVAN L. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2017)
This study investigated the distribution, frequency and properties of restriction enzymes on genomic DNA of SBE I and II to facilitate production of modified starch in cassava. Genomic DNA of starch branching enzyme I and II were amplified, cloned, sequenced and restriction enzyme analyses conducted with bioinformatics tools. Twenty-two restriction enzymes’ sites of 17 restriction enzymes were evenly distributed on the circular restriction map of SBE I gene genomic DNA. Three restriction enzymes produced blunt DNA ends, six enzymes produced 5’ overhang while seven enzymes left 3’ overhang at the end of their DNA cutting activity. Seven enzymes were sensitive to DNA methylation by N6-methyladenosine while 88.2% of the restriction enzymes that cut SBE I DNA with lambda DNA as their substrate. Similarly, the genomic DNA of SBE II had 30 restriction sites cut by 22 restriction enzymes. Seven enzymes produced blunt DNA end, 12 left 5’ DNA end and three produced 3’ DNA end. About 36.4%, 13.6%, 2% and 9.1% of the restriction enzymes were sensitive to N6-methyladenosine, N6- methylcytosine, N4-methylcytosine and N5-methylcytosine DNA methylation, respectively. The study concluded that cassava SBE I and II genomic DNAs contain adequate restriction enzymes’ sites with appropriate properties relevant for manipulation of starch biosynthesis.